Concepts and Measures of Outreach and Sustainability in Microfinance Institutions - Ghising, Tilak (Nepal Journal of Multidisciplinary Research, 2023)
This paper investigates the ideas of outreach and sustainability in South Asian Microfinance Institutions (MFIs), assessing their effectiveness in reaching financially disadvantaged individuals. The literature review emphasizes MFIs' social goals and the need for a comprehensive impact assessment. The study, utilizing a mixed-method approach, conducts a descriptive survey with 400 respondents in Madhesh Pradesh, Nepal, employing statistical tools like SPSS and Excel. Findings reveal varied perspectives on MFIs' positive effects on education, income, and community dynamics. The assessment of outreach efforts considers mission alignment, geographical scope, and collateral requirements, showing a moderate alignment, broad reach, and moderate collateral needs. The study highlights the intricate role of MFIs in addressing socio-economic challenges, emphasizing the necessity for nuanced understanding in the microfinance sector.